Coronin Enhances Actin Filament Severing by Recruiting Cofilin to Filament Sides and Altering F-Actin Conformation. Issue 19 (25th September 2015) - Mikati, Mouna A.; Breitsprecher, Dennis; Jansen, Silvia; Reisler, Emil; Goode, Bruce L.
Abstract: High rates of actin filament turnover are essential for many biological processes and require the activities of multiple actin-binding proteins working in concert. The mechanistic role of the actin filament severing protein cofilin is now firmly established; however, the contributions of other conserved disassembly-promoting factors including coronin have remained more obscure. Here, we have investigated the mechanism by which yeast coronin (Crn1) enhances F-actin turnover. Using multi-color total internal reflection fluorescence microscopy, we show that Crn1 enhances Cof1-mediated severing by accelerating Cof1 binding to actin filament sides. Further, using biochemical assays to interrogate F-actin conformation, we show that Crn1 alters longitudinal and lateral actin–actin contacts and restricts opening of the nucleotide-binding cleft in actin subunits. Moreover, Crn1 and Cof1 show opposite structural effects on F-actin yet synergize in promoting release of phalloidin from filaments, suggesting that Crn1/Cof1 co-decoration may increase local discontinuities in filament topology to enhance severing. Graphical abstract: Highlights: Yeast coronin accelerates binding of cofilin to actin filament sides. Yeast coronin enhances cofilin-mediated actin filament severing. Yeast coronin alters lateral and longitudinal contacts in F-actin. Yeast coronin and cofilin induce distinct conformational effects on F-actin.